2011
DOI: 10.1159/000322901
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressant Prograf® (Tacrolimus) Induces Histopathological Disorders in the Peritubular Tissue of Rat Testes

Abstract: Treatment with tacrolimus (FK-506) has been shown to induce a significant decrease in the number of spermatocytes, spermatids, and Sertoli cells. Regarding the importance of the peritubular tissue for the maintenance of Sertoli cells, the integrity of the cellular and extracellular components of the peritubular tissue was evaluated in adult rats that were treated with 1 mg/kg/day of FK-506 for 30 and 60 days. Testicular sections were used for a quantitative analysis of the peritubular cells (PCs) and were subm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 82 publications
(59 reference statements)
1
11
0
Order By: Relevance
“…Thus, caspase‐3 immunolabelling and ultrastructural features are used for the identification of apoptotic cell death (Caneguim et al. ; Faloni et al. ; Longhini et al.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, caspase‐3 immunolabelling and ultrastructural features are used for the identification of apoptotic cell death (Caneguim et al. ; Faloni et al. ; Longhini et al.…”
Section: Discussionmentioning
confidence: 99%
“…However, it has been reported that the TUNEL method should be combined with other markers to obtain a definitive identification of apoptotic cells (Danial & Korsmeyer, 2004;Cerri, 2005;Cerri & Katchburian, 2005). Thus, caspase-3 immunolabelling and ultrastructural features are used for the identification of apoptotic cell death (Caneguim et al 2011;Faloni et al 2012;Longhini et al 2013;Beltrame et al 2015). Strong immunolabelling for caspase-3 was observed in the cells of lamina propria, primarily in the mucosal penetration stage of the eruptive process, i.e., in the 16-day-old rats.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations